Assessment of CHA2DS2-VASc score for predicting cardiovascular and cerebrovascular outcomes in acute myocardial infarction patients. Issue 28 (July 2018) - Li, Chen-Yu; Chang, Chee-Jen; Chung, Wen-Jung; Lin, Cheng-Jui; Hsueh, Shu-Kai; Lee, Chien-Ho; Wu, Chiung-Jen; Tsai, Tzu-Hsien; Cheng, Cheng-I
Abstract : Abstract: Although established guidelines currently recommend the use of the CHA2 DS2 -VASc score for evaluating embolic risk in AF patients, few studies have evaluated the use of the CHA2 DS2 -VASc score for predicting cardiovascular outcomes in patients with acute myocardial infarction (AMI). The aim of this study was to determine whether CHA2 DS2 -VASc score is a predictor of a major adverse cardiocerebral vascular event (MACCE) in AMI patients. This study analyzed data in the Taiwan National Health Insurance Research Database from January 2008 to December 2012. Cardiovascular outcomes were analyzed according to the baseline characteristics, presence of AF, and CHA2 DS2 -VASc score. Twenty nine thousand four hundred fifty-two patients with non-fatal AMI, 1171 patients (8.3%) were with AF. The Cox regress model showed with the exception of women sex and peripheral artery disease, all the baseline characteristics considered risks in CHA2 DS2 -VASc scores were independently associated with the increased incidence of MACCE within 1 year after AMI. A CHA2 DS2 -VASc score of <5 had negative predictive values of 93.37% for recurrent MI, 98.45% for stroke, 94.86% for HF admission, 98.83% for mortality, and 87.80% for MACCE. Regardless of the presence of AF, the CHA2 DS2 -VASc score was correlated with 1-year MACCE. The CHA2 DS2 -VASc score was correlated with 1-year MACCE in AMI patients who were discharge alive. The CHA2 DS2 -VASc score is useful predictor for 1 year MACCE in patients with AMI.